2014
DOI: 10.1039/c3dt52957f
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular excimer formation in hexakis(pyrenyloxy)cyclotriphosphazene: photophysical properties, crystal structure, and theoretical investigation

Abstract: A hexakis(pyrenyloxy)cyclotriphosphazene is synthesized by the reaction of N3P3Cl6 with 2-hydroxypyrene, and its excimer emission through intramolecular interactions in solution and in the solid state has been investigated by fluorescence spectroscopy and X-ray crystallography. Thermal and electrochemical properties were investigated. A DFT benchmark study has been performed to evaluate the intramolecular interactions and molecular orbital levels by comparing with the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 47 publications
4
8
0
Order By: Relevance
“…The distances of the phenoxy and naphthoxy groups for compounds 6 and 8 are illustrated in Figure 9. The selected intramolecular naphthoxy groups were in the range of 3.79 to 3.98 Å, which is within the accepted range for ππ interaction of less than 4.0 Å [46]. According to the results of the DFT calculations, while excimer emissions occurred within the molecules in compounds 6 and 8, monomer emissions occurred in compounds 5 and 7, but they were not within the molecules, and the theoretical results were in perfect harmony with the fluorescence results.…”
Section: Computational Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The distances of the phenoxy and naphthoxy groups for compounds 6 and 8 are illustrated in Figure 9. The selected intramolecular naphthoxy groups were in the range of 3.79 to 3.98 Å, which is within the accepted range for ππ interaction of less than 4.0 Å [46]. According to the results of the DFT calculations, while excimer emissions occurred within the molecules in compounds 6 and 8, monomer emissions occurred in compounds 5 and 7, but they were not within the molecules, and the theoretical results were in perfect harmony with the fluorescence results.…”
Section: Computational Resultssupporting
confidence: 68%
“…This bathochromic shift of compounds 6 and 8 was very similar to intermolecular excimer emission, and it is well known that intermolecular excimer formation is a concentration-dependent phenomenon and does not occur in dilute media [45]. In addition, the dissolution medium of compounds can affect monomer and excimer formation [46,47]. As can be seen in Figure 4 To evaluate the effect of concentration on the photophysical behaviors of compounds 5-8, the UV-Vis absorption and fluorescence emission spectra were examined at different concentrations in various solvents, such as hexane, dichloromethane (DCM), THF, ethanol, and water ( Figures S11-S18).…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 58%
“…Pyrene excimer formation is a well-known phenomenon in organic solutions. In our previous work hexakis(pyrenyloxy) cyclotriphosphazene exhibited an intramolecular excimer emission arising from the non-covalent π-π and CH-π stacking interactions among the pyrenyloxy moieties which were investigated by fluorescence spectroscopy [21]. Compound 4 exhibits a fluorescence maximum near 448 nm, where most of the incident radiation is absorbed by the pyrene phosphazene parts and not the fullerene which is coherent with the previous results.…”
supporting
confidence: 71%
“…Importantly, the UV-Vis electronic absorption wavelengths of compounds 3a-3d were similar to those of their precursor Schiff bases (2a-2d), which showed that there was no effective ground state interaction with the appended Schiff base on the cyclotriphosphazene scaffold. On the other hand, the absorbances of compounds 3a-3d were much higher than those of the corresponding Schiff bases (2a-2d) at the same concentration, which was most probably due to the increasing number of absorbing Schiff base groups on the cyclotriphosphazene scaffold [51]. The molar absorption coefficients of 3a-3d were as high as 10 4 to 10 5 L mol −1 cm −1 , which were determinative for ππ * state transition characteristics of cyclotriphosphazene derivatives (3a-3d) [52].…”
Section: Uv-vis Absorption Properties Of 3a-3dmentioning
confidence: 89%